CHARACTERIZATION OF PAN-AFRICAN MOBILE BELT DEFORMATIONS OF SOUTHERN MARADI (SOUTH NIGER) - Kankara, I. A.; Konate, M.; Baraou, I. S. (FUDMA JOURNAL OF SCIENCES, 2023)
This present paper discusses the characterization of Pan African Mobile belt deformation of South Maradi. The methodology adopted was mainly primary data, and in that, in the deformation characterization, a multidisciplinary approach has been implemented, including geophysical correlations, cartographic and petrostructural observations. This approach has made it possible to establish a map of the geological formations of the area. The result shows that during the two episodes/phases, the setting of granitoids was associated with the re-playing of the regional shear-zones. The radiometric dating of the rocks revealed that Pan-African deformation phases affected both paleo-proterozoic and Neo-proterozoic formations. In the findings, the analysis highlighted at least three (3) deformational phases, noted D1, D2 and D3. The D2 Pan-African deformation phase, also ductile, consists of two (2) episodes (D2a and D2b) The more brittle D3 phase was associated with two (2) episodes of strain-slip schistocity; one of orientation N800 to N1200 (S3) followed by a second orientation of N400 (S4)